2012
DOI: 10.1002/mrm.24425
|View full text |Cite|
|
Sign up to set email alerts
|

Do dynamic‐based MR knee kinematics methods produce the same results as static methods?

Abstract: MR-based methods provide low risk, noninvasive assessment of joint kinematics; however, these methods often use static positions or require many identical cycles of movement. The study objective was to compare the 3D kinematic results approximated from a series of sequential static poses of the knee with the 3D kinematic results obtained from continuous dynamic movement of the knee. To accomplish this objective, we compared kinematic data from a validated static MR method to a fast static MR method, and compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 41 publications
0
44
0
1
Order By: Relevance
“…Although computed tomography (CT) has considerable utility for assessing patellofemoral kinematics, 27-32 the lack of ionization radiation makes magnetic resonance an attractive modality. 3-6,33 …”
Section: Discussionmentioning
confidence: 99%
“…Although computed tomography (CT) has considerable utility for assessing patellofemoral kinematics, 27-32 the lack of ionization radiation makes magnetic resonance an attractive modality. 3-6,33 …”
Section: Discussionmentioning
confidence: 99%
“…Sequential static imaging provides similar accuracies for patellar kinematics (1.02°/0.88 mm [34]). However, static imaging cannot capture the dynamic muscle and inertial effects that arise in active motion and affect joint mechanics [15]. Multi-slice dynamic imaging has been proposed to supplant sequential static imaging [15].…”
Section: Discussionmentioning
confidence: 99%
“…However, static imaging cannot capture the dynamic muscle and inertial effects that arise in active motion and affect joint mechanics [15]. Multi-slice dynamic imaging has been proposed to supplant sequential static imaging [15]. However, real-time implementations of multi-slice imaging are currently only viable for slow, quasi-static motion (20 s/cycle).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They demonstrated the importance of normal knee kinematics and highlighted the value of kinematic MR imaging in clinical assessment of the knee post-surgery or in modelling the impact of altered knee kinematics on contact mechanisms. Several research studies have however demonstrated that considerable differences exist between passive and active knee motion as a result of the missing active muscle forces applied to the joint structures [Shellock 1992, Shellock 1993, Brossmann 1993, Smith 2003, d'Entremont 2013. …”
Section: Connolly Et Al Studied Patellofemoral Kinematics Usingmentioning
confidence: 99%